Demystifying Traumatic Experiences and Complex Effects in People with HIV and Post-Traumatic Stress Disorder in Tennessee - L. Lauren Brown; Almariana J. Acuña; Amna Osman; Lloyda B. Williamson; Carolyn M. Audet; Megan L. Wilkins; Jessica M. Sales; Samantha V. Hill; Jill Foster; April C. Pettit; Latrice C. Pichon (Health Equity)
Background: Compared with the general public, people with HIV (PWH) experience more psychological trauma and higher rates of post-traumatic stress disorder (PTSD), yet limited research explores how PWH may uniquely experience trauma. The primary goal of this study was to investigate trauma exposure typologies and sequelae among PWH to inform trauma screening and interventions. Methods: Qualitative interviews were conducted with a convenience sample of 20 PWH with PTSD, receiving services from an urban, Tennessee-based HIV Service Organization. Interview guides were conducted to gain a rich understanding of exposure types from the Life Events Checklist-5 (LEC-5), explore potential social determinants of trauma, and uncover effects of chronic trauma or traumata. Thematic content analysis was used to examine typologies and effects. Results: Exposure typologies appeared as social determinants of trauma, including molestation as the most common followed by racial trauma, community violence, incarceration, addiction, interpersonal violence, poverty cycles, and stigma. Standard PTSD symptoms were reported in addition to emerging effects of complexity, synergism, and resilience. Complex effects spanned socioecological contexts and included sequelae of affective dysregulation, negative self-concept/self-organization, and disturbances in relationships. Conclusion: Many typologies were not well accounted for in the LEC-5, underscoring the potential to miss exposure types and thus treatment indication. Similarly, effects expanded beyond standard PTSD symptoms, suggesting that nuanced treatment needs may also be overlooked. Findings are consistent with literature indicating the need for updated trauma screening and assessment measures to most comprehensively and accurately direct treatment needs.